Prevalence of Colonic Diverticulosis in Patients Affected by Ulcerative Colitis: A Prospective Study. (October 2016) - Cassieri, Claudio; Pica, Roberta; Avallone, Eleonora V.; Zippi, Maddalena; Crispino, Pietro; De Nitto, Daniela; Paoluzi, Paolo; Brandimarte, Giovanni; Lecca, Piera Giuseppina; Elisei, Walter; Picchio, Marcello; Tursi, Antonio
Abstract : Background: Diverticulosis of the colon is an acquired condition that results from herniation of the mucosa and submucosa through defects in the muscular layer. The true prevalence of colonic diverticulosis is difficult to measure because most individuals are asymptomatic. In particularly, in literature, there are few studies about the prevalence of colonic diverticulosis in patients affected by ulcerative colitis (UC). Goals: To investigate the prevalence of colonic diverticulosis in UC and in adult patients referred in a single center. Study: Consecutive patients, referred to our institution to undergo a colonoscopy for colorectal cancer screening and/or for UC assessment, between January 1, 2014 and December 31, 2014, were studied. Results: Six hundred five consecutive patients were studied: 438 (72.4%) due to colorectal cancer screening (group A) and 167 (27.6%) for UC assessment (group B). Prevalence of colonic diverticulosis was higher in group A than group B (27.8% vs. 10.8%, P <0.0001). Female gender in patients with colonic diverticulosis was higher in group A than group B (55.7% vs. 22.2%, P =0.0106). Sigma and left colon was mainly involved in group A than group B (97.6% vs. 66.7%, P =0.0001), whereas in group B the right colon was mainly involved in group B versus group A (22.2% vs. 0.8%, P =0.0009). Conclusions: Prevalence of colonic diverticulosis was significantly lower in patients with UC than in control group. UC may, therefore, be a protective factor for colonic diverticulosis occurrence.